Etiology, pathology, and host-impaired immunity in medical implant-associated infections - Ihtisham Ul Haq; Taj Ali Khan; Katarzyna Krukiewicz (Elsevier, 2024)
Host impaired immunity and pathogens adhesion factors are the key elements in analyzing medical implant-associated infections (MIAI). The infection chances are further influenced by surface properties of implants. This review addresses the medical implant-associated pathogens and summarizes the etiology, pathology, and host-impaired immunity in MIAI. Several bacterial and fungal pathogens have been isolated from MIAI; together, they form cross-kingdom species biofilms and support each other in different ways. The adhesion factors initiate the pathogen's adherence on the implant's surface; however, implant-induced impaired immunity promotes the pathogen's colonization and biofilm formation. Depending on the implant's surface properties, immune cell functions get slow or get exaggerated and cause immunity-induced secondary complications resulting in resistant depression and immuno-incompetent fibro-inflammatory zone that compromise implant's performance. Such consequences lead to the unavoidable and straightforward conclusion for the downstream transformation of new ideas, such as the development of multifunctional implant coatings.